THE DYNAMICS OF LAND COVER CHANGE AND LEVEL OF SUSTAINABILITY DEVELOPMENT IN DEPOK CITY - Rosandi, Vely Brian; Pravitasari, Andrea Emma; Rachendra, Andra Septina (Diponegoro University, 2024)
The massive development of Depok City has had an impact on improving the economic level but has also caused a decline in environmental sustainability and quality. This research aims to determine trends in land cover change and predictions for the future as well as the level of sustainability of development in Depok City. Land cover change trends in Depok City were carried out using the overlay method in ArcGIS software using land cover data for 2000, 2009, and 2019. Land cover changes were predicted until 2039 using the Land Change Modeler (LCM) analysis method with a business-as-usual scenario (BAU). Meanwhile, sustainability status is analyzed using the Rapfish Multidimensional Scaling (MDS) method using data/attributes from economic, social, and environmental dimensions. The research results show that changes in land cover in Depok City from 2000 - 2019 were dominated by agriculture to residential areas. Some open land is expected to experience a significant decline by 2039, while residential areas will continue to increase. The results of the MDS Rapfish analysis show that sub-districts in Depok City have different sustainability statuses, both in economic, social, and environmental dimensions.